How Far Is Eastern Europe from Brussels? - Sahay, Ratna (IMF Working Papers; Working Paper ;, 1998)
The current destination of Central and Eastern European countries-explicitly for some, implicitly for all-is Brussels. The concept of the distance from Brussels is multi-dimensional. One simple measure, not without theoretical and empirical justification, is physical distance. This paper's focus, however, lies more in the distances in time and economic space. The paper first compares income gaps between Central and Eastern European and European Union (EU) countries, then evaluates recent economic performance in Central and Eastern Europe in light of EU standards. Finally; addresses the question of how long it will take the Central and Eastern European countries to close the income gap with EU countries.